Prospective assessment of function and cold-intolerance following revascularization for hypothenar hammer syndrome. Issue 12 (December 2020) - Malsagova, A.T.; van Burink, M.V.; Smits, E.S.; Zöphel, O.T.; Stassen, C.M.; Botman, J.M.J.; Rakhorst, H.A.
Abstract: Ulnar artery revascularization in hypothenar hammer syndrome has repeatedly been shown to reduce ischaemic symptoms, however with varying graft patency percentages. This study prospectively assesses the effect of revascularization surgery with a vein graft using validated questionnaires in seven patients. The Disabilities of the Arm, Shoulder and Hand (DASH) and the Cold Intolerance Symptom Severity (CISS) questionnaires have been used to compare the preoperative and postoperative functionality and cold intolerance. All patients showed improvement in either functionality, or cold intolerance, or both from disabled to nearly normalized levels and resumed their occupation at final follow-up (mean of 28 months). Strikingly this was also the case in a patient with graft stenosis. Patients with the highest preoperative questionnaire scores showed most postoperative improvement. In conclusion, revascularization surgery seems to improve the symptomatology irrespective of graft patency. Questionnaires can be a valuable contribution to quantify and to follow the symptomatology in hypothenar hammer syndrome.